2014
DOI: 10.1186/1472-6882-14-156
|View full text |Cite
|
Sign up to set email alerts
|

Polysaccharides from Liriopes Radix ameliorate streptozotocin-induced type I diabetic nephropathy via regulating NF-κB and p38 MAPK signaling pathways

Abstract: BackgroundThe polysaccharides from Liriopes Radix (PSLR) has been indicated to ameliorate insulin signaling transduction and glucose metabolism. We aimed to investigate whether PSLR exerts an ameliorative effect on renal damage in diabetes induced by streptozotocin.MethodsDiabetes was induced with STZ (60 mg/kg) by intraperitoneal injection in rats. Two weeks after STZ injection, rats in the treatment group were orally dosed with PSLR (200 and 300 mg/kg/day for 8 weeks. The normal rats were chosen as nondiabet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 31 publications
2
12
0
Order By: Relevance
“…In addition, oxidative stress is correlated with obesity and hyperandrogenism [ 45 ]. Increased oxidative stress could also induce directly genetic variation by DNA damage, and epigenetic change including elevated DNA methylation levels, which both play important roles in the pathogenesis of cancer [ 46 , 47 ]. Up-regulation of IL-18 by SCFA products [ 48 ] and elevated production of methylketones in gut by synbiotic [ 49 ] might decrease inflammatory markers.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, oxidative stress is correlated with obesity and hyperandrogenism [ 45 ]. Increased oxidative stress could also induce directly genetic variation by DNA damage, and epigenetic change including elevated DNA methylation levels, which both play important roles in the pathogenesis of cancer [ 46 , 47 ]. Up-regulation of IL-18 by SCFA products [ 48 ] and elevated production of methylketones in gut by synbiotic [ 49 ] might decrease inflammatory markers.…”
Section: Discussionmentioning
confidence: 99%
“…More evidences show the links between p38 MAPK and inflammation, cell cycle, cell death, development, cell differentiation, senescence, and tumorigenesis in specific cell types [ 8 ]. Recent studies have shown that inflammation is associated with the development and progression of DN, implying that inflammatory mechanisms may play a pivotal role in the disease process [ 10 , 11 ]. The p38 MAPK pathway plays a major role in the regulation of inflammatory responses [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…This hypothesis was further verified by western blotting. Beta-cell apoptosis in the pancreas, insulin resistance, and hyperglycemia induce the excessive production of inflammatory mediators, iNOS, and COX-2, through activation of the NF-kB signaling pathway in DN (Lu et al, 2014). Moreover, the phosphorylation of serine residues in the insulin receptor (IRS-1) results in diminished enzymatic activity in the PI3K/Akt pathway in DN.…”
Section: Discussionmentioning
confidence: 99%